Multi-metal Oxides Used as Catalyst and Oxygen Carrier for Reforming and Partial Oxidation of Bio-methane - Francesco Miccio; Lucrezia Polchri; Giuseppina Iervolino; Frederic Monteverde (Chemical Engineering Transactions)
Partial oxidation and reforming of methane are well-known methods to obtain mixtures of CO, CO2 and H2 that can be separated or used in other processes, e.g. the synthesis of methanol. The aim of this study is to go beyond commercially available catalysts containing critical and expensive raw ingredients and find new, cheaper and more durable candidates for reforming and partial oxidation. A multi-metal oxide (MMO), mostly known like “high-entropy” oxide, was developed, free of noble metals through conventional a solid-state reaction synthesis, and compared to some mixtures made of widely used oxides here reported: CeO2/Al2O3, CeO2/Al2O3/CuO and CeO2/Al2O3/CuO/Ca(OH)2. The performance of the MMO was studied and compared to the oxide mixtures above reported. The materials were obtained as discrete granules of irregular shape in the range of 1-2 mm by pelletizing them and further hot consolidation. TPR analysis and tests in a laboratory scale quartz reactor with feeding lines of different gas mixtures were carried out. Promising results in terms of reducibility, CH4 conversion (up to 95%) and CO selectivity (up to 60%) were achieved for CeO2/Al2O3 and MMO, the latter showing good behavior over repeated cycles.